Altered appetite in Crohn’s Disease: deconstructing the enteroendocrine axis using fMRI - Thapaliya, Gita (2019)
Reduced appetite has been observed in patients with ileal Crohn’s disease, which has been attributed to the upregulation of enteroendocrine cells and the consequent increase of satiety hormones secretion, therefore possibly negatively affecting appetite signalling to the central nervous system. The specific hypotheses to be tested in this thesis were that Crohn’s disease patients with ileal inflammation, when compared with Crohn’s disease patients with colonic inflammation and healthy controls, will show A) an alteration in brain-gut stimulation, B) an increase in the postprandial plasma enteroendocrine peptides response (CCK, GLP-1 and PYY) with associated alteration in appetite scores, C) a change in eating behaviour, and D) an alteration in brain structure and resting-state functional connectivity.